Addressing & understanding citizens' perceptions of homelessness: a cross-European study. (13th November 2019) - Taylor, O; Loubiere, S; Tinland, A; Loundou, A; Auquier, P; EU, HOME; Ornelas, Jose
Abstract: Objective: Addressing Citizen's perspectives on homelessness is crucial for the design of effective and durable policy responses, and available research in Europe is not yet substantive. We aim to explore citizens' opinion about homelessness and to explain the differences in attitudes within the general population of eight European countries: France, Ireland, Italy, the Netherlands, Poland, Portugal, Spain, and Sweden. Methods: A nationally representative telephone survey of European citizens was conducted in 2017. Three domains were investigated: Knowledge, Attitudes, and Practices about homelessness. Based on a multiple correspondence analysis, a generalized linear model for clustered and weighted sample was used to probe the associations between groups with opposing attitudes, adjusted for sociodemographic characteristics. Results: The response rate ranged from 30.4% to 33.5% (N = 5, 295). Most respondents (57%) had poor knowledge about homelessness. Respondents who thought the government spent too much on homelessness, homeless people should be responsible for housing, people remain homeless by choice, or homelessness keeps capabilities/empowerment intact clustered together (negative attitudes, 30%). Respondents who were willing to pay taxes, welcomed a shelter, or acknowledged homeless people may lack some capabilities (i.e. agreed on discrimination in hiring) made another cluster (positive attitudes, 58%). Older respondents (OR = 0.99; p=.011), those living in rural areas (OR = 0.78, p<.001), those with a poor level of knowledge about homelessness (OR = 0.68, p=.007), and those from France and Poland (p<.001) were less likely to report positive attitudes. Conclusions: Although it is clear that there is strong support for increased government action and more effective solutions for Europe's growing homelessness crisis, there also remain public opinion barriers rooted in enduring negative perceptions. Key messages: A majority of European citizens reported positive attitudes towards Homelessness. There is strong support for increased government action and more effective solutions for Europe's growing homelessness crisis.